Earnings expectations and educational sorting: An ex-ante perspective on returns to university education - Nikolay Angelov; Per-Olov Johansson; Mikael Lindahl; Ariel Pihl (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
We estimate means and distributions of ex-ante treatment effects for obtaining university education relative to high school. To achieve this, we conducted a survey which elicited earnings expectations associated with counterfactual educational choices for a sample of highschool students in Stockholm. We find average ex-ante returns to university to be 36%, with higher returns for females, those with high SES backgrounds, and high math scores. The returns vary considerably and are highest for those that choose university, but also positive and sizable for those who do not. Our results imply that students sort into education based on their comparative advantage. Nevertheless, our results suggest that an OLS estimator of the returns to university education should be expected to be quite similar to the average treatment on the treated effect for university education. Additionally, we find evidence that the positive ex-ante earnings returns to high paying fields, among those that do not choose these fields, can (partly) be reconciled by individuals expecting to be compensated through higher non-pecuniary returns to those fields.
Keywords: I26; J24; 330; Ex-ante treatment effects; returns to university; educational sorting; subjective expectations